2014
DOI: 10.1539/sangyoeisei.b13003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Visceral Fat Measurements and a Weight Loss Support Web System on Visceral Fat Loss in a Workplace Setting: Insights from a JVALUE2 (Japanese Study of Visceral Adiposity and Lifestyle Information; Utilization and Evaluation)

Abstract: A parallel randomized trial involving the employees of our company was performed and we scientifically verified the effects of an occupational health programs. Objective study of occupational health activities and measures were enabled by devising methods and procedures, e.g., applying the waiting-list method for the control group. This approach will lead to appropriate selection and precise implementation of evidence-based measures in occupational health in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…6 Furthermore, as a population approach, health promotion has been underway for workers. 7,8 In work places, it has been found that the achievement of results is greatly affected by the effectiveness of the health promotion program for employees, as well as organizational factors such as the employee support from manager and the scheme by which the programs are offered. 9,10 Various studies have analyzed the factors that affect the outcomes of health promotion programs in the workplace, collected data on examples of good practice, and investigated common factors between them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Furthermore, as a population approach, health promotion has been underway for workers. 7,8 In work places, it has been found that the achievement of results is greatly affected by the effectiveness of the health promotion program for employees, as well as organizational factors such as the employee support from manager and the scheme by which the programs are offered. 9,10 Various studies have analyzed the factors that affect the outcomes of health promotion programs in the workplace, collected data on examples of good practice, and investigated common factors between them.…”
mentioning
confidence: 99%
“…Based on the results of these examination, most companies provide feedback to employees to promote lifestyle improvements and encourage hospital visits 6 . Furthermore, as a population approach, health promotion has been underway for workers 7,8 …”
mentioning
confidence: 99%